The genome sequence of the Common Sycamore Aphid, Drepanosiphum platanoidis (Schrank, 1801) [version 1; peer review: 2 approved] - Reuben James; Liam M. Crowley (Wellcome Open Research, 2023)
We present a genome assembly from an individual female Drepanosiphum platanoidis (the Common Sycamore Aphid; Arthropoda; Insecta; Hemiptera; Aphididae). The genome sequence is 284.5 megabases in span. Most of the assembly is scaffolded into 15 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 19.45 kilobases in length. Gene annotation of this assembly on Ensembl identified 13,286 protein coding genes.